Structure and binding specificity of the receiver domain of sensor histidine kinase CKI1 from Arabidopsis thaliana - Pekárová, Blanka; Klumpler, Tomáš; Třísková, Olga; Horák, Jakub; Jansen, Séverine; Dopitová, Radka; Borkovcová, Petra; Papoušková, Veronika; Nejedlá, Eliška; Sklenář, Vladimír; Marek, Jaromír; Zídek, Lukáš; et al. (The Plant journal, 2011)
Multistep phosphorelay (MSP) signaling mediates responses to a variety of important stimuli in plants. In Arabidopsis MSP, the signal is transferred from sensor histidine kinase (HK) via histidine phosphotransfer proteins (AHP1-AHP5) to nuclear response regulators. In contrast to ancestral two-component signaling in bacteria, protein interactions in plant MSP are supposed to be rather nonspecific. Here, we show that the C-terminal receiver domain of HK CKI1 (CKI1(RD) ) is responsible for the recognition of CKI1 downstream signaling partners, and specifically interacts with AHP2, AHP3 and AHP5 with different affinities. We studied the effects of Mg²⁺, the co-factor necessary for signal transduction via MSP, and phosphorylation-mimicking BeF₃⁻ on CKI1(RD) in solution, and determined the crystal structure of free CKI1(RD) and CKI1(RD) in a complex with Mg²⁺. We found that the structure of CKI1(RD) shares similarities with the only known structure of plant HK, ETR1(RD) , with the main differences being in loop L3. Magnesium binding induces the rearrangement of some residues around the active site of CKI1(RD) , as was determined by both X-ray crystallography and NMR spectroscopy. Collectively, these results provide initial insights into the nature of molecular mechanisms determining the specificity of MSP signaling and MSP catalysis in plants.
Keywords: mutace; Arabidopsis Proteins; Protein Structure, Tertiary; Histidine; Recombinant Fusion Proteins; terciární struktura proteinů; rekombinantní fúzní proteiny; Phosphotransferases; proteinkinasy; Sensitivity and Specificity; signální transdukce; Mutation; senzitivita a specificita; mapování interakce mezi proteiny; krystalografie rentgenová; Signal Transduction; proteiny huseníčku; Models, Molecular; Protein Interaction Mapping; molekulární modely; fosforylace; histidin; Protein Kinases; Arabidopsis; fosfotransferasy; Crystallography, X-Ray; Phosphorylation